2008
DOI: 10.1128/aac.00155-07
|View full text |Cite
|
Sign up to set email alerts
|

Drosomycin-Like Defensin, a Human Homologue ofDrosophila melanogasterDrosomycin with Antifungal Activity

Abstract: Innate antifungal defense in Drosophila melanogaster relies on the activation of the Toll molecule and the release of drosomycin, a defensin-like molecule with antifungal properties. Ten human homologues of Toll have been described, with central roles in activation of the innate host defense. In the present study, we report a putative human homologue of the Drosophila-derived drosomycin, designated drosomycin-like defensin (DLD). Synthetic DLD displays a broad spectrum of activity against Aspergillus spp. and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 29 publications
1
18
0
Order By: Relevance
“…Consistent with this hypothesis, both charybdotoxin and defensin from Leiurus have short n-loops, but charybdotoxin has the sequence “GKCMN” while the defensin has “GYCAG.” Charybdotoxin also has antimicrobial activity, so while the short n-loop and KCXN motif may be sufficient to indicate toxic activity, the characteristics suggesting antimicrobial activity are less clear. Drosomycin-like defensin (DLD) from humans has activity specifically against filamentous fungi, despite the sequence not having conventional CSH, CS-αβ, or γ-core motifs [80]. …”
Section: Resultsmentioning
confidence: 99%
“…Consistent with this hypothesis, both charybdotoxin and defensin from Leiurus have short n-loops, but charybdotoxin has the sequence “GKCMN” while the defensin has “GYCAG.” Charybdotoxin also has antimicrobial activity, so while the short n-loop and KCXN motif may be sufficient to indicate toxic activity, the characteristics suggesting antimicrobial activity are less clear. Drosomycin-like defensin (DLD) from humans has activity specifically against filamentous fungi, despite the sequence not having conventional CSH, CS-αβ, or γ-core motifs [80]. …”
Section: Resultsmentioning
confidence: 99%
“…By studying the comparative kinetics of mRNA induction of the two major antifungal peptides, Drs and Mtk, which are under the control of the Tl pathway, we found that the Tl pathway was rapidly and efficiently activated by Zygomycetes and A. fumigatus to a comparable degree. Nonetheless, we cannot exclude selective degradation of antifungal peptides in D. melanogaster by Zygomycetes toxins (40), or that Zygomycetes spores might be less susceptible to the effects of D. melanogaster antifungal peptides than A. fumigatus spores (41).…”
Section: Discussionmentioning
confidence: 99%
“…Interleukin-37 (IL-37) is considered to be a fundamental inhibitor of innate immunity decreasing the production of pro-inflammatory cytokines and so protecting against inflammatory and autoimmune diseases. hBD-3, but not hBD-1, -2, and -4, up-regulates the mRNA and protein expression of IL-37 in human keratinocytes and stimulates the release of IL-37 into culture supernatants [98]. IL-37 is highly expressed in psoriatic skin and so hBD-3 may have a role in therapy for cutaneous inflammatory diseases through regulation of IL-37 expression.…”
Section: Peptides With Immunomodulatory Activitymentioning
confidence: 99%
“…[113]). These include the cathelicidinrelated peptide LL-37 [44], the ␤-defensins hBD-1 [8], hBD-2 [6], and hBD-3 [53], chimerin [2,109], several chemokines such as CCL20/MIP-3␣ [129], dermcidin [93], drosomycin-like defensin (DLD) [98], psoriasin (S100A7) [48] and the structurally similar koebnerisin (S100A15) [119], and RNase 7 [54]. In addition, neuronal/neuroendocrine peptides such as substance P, CGRP, ␣-MSH, NPY, TRH, and VIP present in the skin show varying degrees of antibacterial activity [5].…”
Section: Humanmentioning
confidence: 99%